Innovative Service Experiences of Travellers Visiting High-Tech Hotels: The Case of Eccleston Square Hotel, London - Çakar, Kadir; Aykol, Şehmus (Turizam, 2019)
The purpose of the current qualitative research on travellers’ behaviors and attitudes visiting high-tech hotels is to examine and understand the effects of innovative service experiences. With the aim of contributing to knowledge in the field of service research, this paper has employed user-generated content (UGC) within the context of a qualitative research method. Data was obtained from online reviews left by travellers (n=350) on TripAdvisor who visited the Eccleston Square Hotel in London, which generated the unit of data analysis and was processed through content analysis. Findings of the present study have indicated that the innovative service experiences of travellers visiting the Eccleston Square Hotel reflect many heterogeneous and multidimensional features. These were clustered into a main theme and then subdivided into categories, deriving from identified codes. Results have also revealed that travellers are more disposed towards visiting technologically oriented and equipped hotels that can improve the quality of customer experience while potentially creating a positive impact on their satisfaction levels and intentions to revisit, as well as positive eWOM effects for other travellers. The results of this research provide useful theoretical and managerial implications for both scholars and marketing and general managers of hotels with regard to innovative service experiences. The innovative service experiences of travellers visiting high-tech hotels reflect multidimensional and heterogeneous patterns, as well as positive features, while describing manifold and multifaceted experiences (i.e., restorative, sensory, transformative, cognitive, physical and emotional). These experiences have generated the originality aspect of the current research, as at present there has been no study on such a subject undertaken by scholars.